Environmental conditions regulate the impact of plants on cloud formation - D. F. Zhao (Nature Portfolio, 2017)
Volatile organic compounds (VOC) emitted by vegetation influence cloud formation, yet the impact of environmental stresses remains little known. Here, manipulation experiments reveal insect infestation and heat stress are linked to induced VOC and constitutive VOC emissions shifts, respectively.